The MYH9 Cytoskeletal Protein Is a Novel Corepressor of Androgen Receptors - Chunhua Liu; Zhaoping Liao; Xiuzhi Duan; Pan Yu; Piaoping Kong; Zhihua Tao; Zhihua Tao; Weiwei Liu (Frontiers in Oncology, 2021)
In the progression of castration-resistant prostate cancer (CRPC), the androgen receptor (AR) that serves as a transcription factor becomes the most remarkable molecule. The transcriptional activity of AR is regulated by various coregulators. As a result, altered expression levels, an aberrant location or activities of coregulators promote the development of prostate cancer. We describe herein results showing that compared with androgen-dependent prostate cancer (ADPC) cells, AR nuclear translocation capability is enhanced in androgen-independent prostate cancer (AIPC) cells. To gain insight into whether AR coregulators are responsible for AR translocation capability, we performed coimmunoprecipitation (CO-IP) coupled with LC-MS/MS to screen 27 previously reported AR cofactors and 46 candidate AR cofactors. Furthermore, one candidate, myosin heavy chain 9 (MYH9), was identified and verified as a novel AR cofactor. Interestingly, the distribution of MYH9 was in both the cytoplasmic and nuclear compartments yet was enriched in the nucleus when AR was knocked down by AR shRNA, suggesting that the nuclear translocation of MYH9 was negatively regulated by AR. In addition, we found that blebbistatin, an inhibitor of MYH9, not only promoted AR nuclear translocation but also enhanced the expression of the AR target gene PSA, which indicates that MYH9 represses nuclear AR signaling. Taken together, our findings reveal that MYH9 appears to be a novel corepressor of AR plays a pivotal role in the progression of CRPC.